Analisis Hukum Positif dan Hukum Pidana Islam tentang Pemerasan Dengan Modus Kencan - Syafa Aliyya Alqoyyum; Moh. Imron Rosyadi (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2025)
This study aims to analyze and compare the provisions of Indonesian positive law and Islamic criminal law regarding the criminal act of extortion through fictitious dating schemes, which have recently become increasingly prevalent, particularly targeting tourists. The methodology used is normative legal research with a qualitative approach, presented through descriptive and comparative analysis. The focus of this research lies in identifying the elements of extortion as regulated in Article 368 of the Indonesian Criminal Code (KUHP), distinguishing it from theft and robbery, and examining the concept of extortion in Islamic criminal law as a form of jarimah ta’zir. The findings reveal that extortion through dating schemes is an unlawful act that not only violates positive law but also contravenes moral principles and ethical values in Islamic criminal law. In the Islamic legal context, such acts fall under the category of jarimah ta’zir, with punishments determined by judges based on the severity of the offense and the harm caused. This study is expected to contribute meaningfully to efforts in preventing similar crimes and enhancing public legal awareness.